2013
DOI: 10.1098/rsif.2013.0560
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of particle size distribution of the droplets exhaled by sneeze

Abstract: This work focuses on the size distribution of sneeze droplets exhaled immediately at mouth. Twenty healthy subjects participated in the experiment and 44 sneezes were measured by using a laser particle size analyser. Two types of distributions are observed: unimodal and bimodal. For each sneeze, the droplets exhaled at different time in the sneeze duration have the same distribution characteristics with good time stability. The volume-based size distributions of sneeze droplets can be represented by a lognorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
362
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(380 citation statements)
references
References 54 publications
15
362
1
2
Order By: Relevance
“…The number density, velocity and size distributions of droplets ejected by expiratory events have important implications for transmission, and numerous studies have attempted to measure these characteristics (Duguid 1946;Wells 1955;Morawska et al 2009;Xie et al 2009;Han, Weng & Huang 2013;Bourouiba, Dehandschoewercker & Bush 2014;Scharfman et al 2016;Asadi et al 2019). A single sneeze can generate O(10 4 ) or more droplets, with velocities upwards of 20 m s −1 (Han et al 2013). Coughing generates 10-100 times fewer droplets than sneezing, with velocities of approximately 10 m s −1 , but even talking can generate approximately 50 particles per second (Asadi et al 2019).…”
Section: Droplet Characteristicsmentioning
confidence: 99%
“…The number density, velocity and size distributions of droplets ejected by expiratory events have important implications for transmission, and numerous studies have attempted to measure these characteristics (Duguid 1946;Wells 1955;Morawska et al 2009;Xie et al 2009;Han, Weng & Huang 2013;Bourouiba, Dehandschoewercker & Bush 2014;Scharfman et al 2016;Asadi et al 2019). A single sneeze can generate O(10 4 ) or more droplets, with velocities upwards of 20 m s −1 (Han et al 2013). Coughing generates 10-100 times fewer droplets than sneezing, with velocities of approximately 10 m s −1 , but even talking can generate approximately 50 particles per second (Asadi et al 2019).…”
Section: Droplet Characteristicsmentioning
confidence: 99%
“…From another point of view, several research groups found that aerosol particles exhaled by humans are composed of small droplets of airway-lining fluid (Fiegel et al, 2006;Han, Weng & Huang, 2013), and some of these exhaled droplets contain pathogens, such as influenza viruses (Fabian et al, 2008;Milton, Fabian, Cowling, Grantham & McDevitt, 2013), tuberculosis bacteria (Turner & Bothamley, 2014), and severe acute respiratory syndrome viruses (World Health Organization (WHO), 2009). However, the concentrations of overall culturable bioaerosols in exhaled air from humans were not adequately measured in these reference studies.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the initial ethanol concentration, samples with two constant octanol/water (OCT/W) ratios of 1/99 and 5/95 were selected for detection, and are presented in Figure 4A. [46] It is also possible for chemical identification from such small volume of highly diluted solution. When the OCT/W ratio is 5/95, the profile of the volume of analyte solution in the range of 0.73-0.45 shows weak fluorescence intensity with a minimum volume of analyte solution of ≈9 µL.…”
Section: Minimal Volume Of Analyte Solution For the Spinning Ouzo Dromentioning
confidence: 99%
“…Such volume required for the sample solution is even smaller than a typical size of a drop from sneezing or coughing. [46] It is also possible for chemical identification from such small volume of highly diluted solution. Figure 4C,D shows the FTIR spectra and corresponding profiles of IR absorbance at 1709 cm −1 of octanol nanodroplets produced by ternary OCT/W/E drops with different initial volumes of nonanoic acid aqueous solutions (10 −5 m).…”
Section: Minimal Volume Of Analyte Solution For the Spinning Ouzo Dromentioning
confidence: 99%